The Influence of Teachers’ Emotional Support and Classroom Management Quality On Students’ Learning Satisfaction Level At Sd Gmim 05 Manado - Don Corleon Graciano Zougira; Harol Reflie Lumapow; Shelty Deity Meity Sumual (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the influence of teachers’ emotional support and classroom management quality on students’ learning satisfaction at SD GMIM 05 Manado. The study was motivated by the low level of student enthusiasm and participation during the learning process. This research employed a quantitative approach using an ex-post facto design and a correlational framework. The population consisted of 200 students, with 40 students selected as the sample through Proportional Random Sampling. Data were collected using closed-ended questionnaires with a Likert scale and analyzed through Multiple Linear Regression Analysis using IBM SPSS Statistics. The findings revealed that teachers’ emotional support partially had a positive and significant effect on students’ learning satisfaction, with a significance value of 0.005 < 0.05 and a contribution of 60.2%. Classroom management quality also showed a positive and significant effect, with a significance value of 0.001 < 0.05 and a contribution of 58.7%. Simultaneously, both variables significantly influenced students’ learning satisfaction, with a significance value of 0.001 < 0.05 and an Adjusted R Square value of 67.2%. The study concludes that students’ learning satisfaction is strongly influenced by teachers’ emotional support and effective classroom management. Therefore, schools should strengthen teachers’ socio-emotional competencies and classroom management skills to create more meaningful and satisfying learning experiences for students.